2009
DOI: 10.1061/(asce)ee.1943-7870.0000085
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Musk Fragrances in a Conventional Drinking Water Treatment Plant with Lime Softening

Abstract: Synthetic musk fragrances are common personal care product additives and wastewater contaminants that are routinely detected in the environment. This study examines the presence eight synthetic musk fragrances (AHTN, HHCB, ATII, ADBI, AHMI, musk xylene, and musk ketone) in source water and the removal of these compounds as they flow through a Midwestern conventional drinking water plant with lime softening. The compounds were measured in water, waste sludge, and air throughout the plant. HHCB and AHTN were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…Carbamazepine was selected attending its high recalcitrance and the difficulty to remove this compound from water sources (Golan-Rozen et al, 2011). Galaxolide and tonalide were selected as representative musk fragrances, commonly found in water sources and already detected in human tissues (Golan-Rozen et al, 2011;Wombacher and Hornbuckle, 2009). The main results of the present work propose that exposure to ECs for 26 d had not a huge impact on S. maltophilia planktonic antimicrobial susceptibility.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Carbamazepine was selected attending its high recalcitrance and the difficulty to remove this compound from water sources (Golan-Rozen et al, 2011). Galaxolide and tonalide were selected as representative musk fragrances, commonly found in water sources and already detected in human tissues (Golan-Rozen et al, 2011;Wombacher and Hornbuckle, 2009). The main results of the present work propose that exposure to ECs for 26 d had not a huge impact on S. maltophilia planktonic antimicrobial susceptibility.…”
Section: Introductionmentioning
confidence: 85%
“…Galaxolide and tonalide are two polycyclic musk fragrances whose ecological and human toxicity is still unknown. Nevertheless, these compounds have been detected in human blood, adipose tissue and breast milk (Wombacher and Hornbuckle, 2009). Duedahl-Olesen et al (2005) also found galaxolide in trout samples.…”
Section: Introductionmentioning
confidence: 98%
“…Most studies on SMCs have focused on NMs and PCMs with fewer conducted on MCMs. 1,30,31 NMs and PCMs have been reported in indoor dust, 1,[32][33][34] indoor air, 32,35,36 outdoor air, [37][38][39][40][41][42] biota; 43-48 surface waters; 37,41,49-51 sea water, 37 sediments, 52 wastewater treatment plants (WWTPs); [53][54][55] drinking water, 56 human adipose tissue, 45,57,58 breast milk, 31,[59][60][61] and serum. 59,62 The potential for SMCs to undergo long-range transport is debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Tato látka (a další jí podobné) používaná jako stabilizátor vůně je pravidelnou součástí našich domovů a ostatních budov (Sofuoglu et al, 2010;Kubwabo et al, 2012). Nalézáme ji však i exteriérech na místech, kde bychom ji nečekali: v pitné vodě (Wombacher, Hornbuckle, 2009), rybách (Rimkus et al, 1997) a dokonce i v mateřském mléce (Lignell et al, 2008).…”
Section: Výrobky a Přípravky Uvolňující Vocunclassified